The effect of lubricants with mineral additives on friction in supports of spindle assemblies - V. A. Ilyinykh (Омский научный вестник)
Currently, the task of increasing the reliability and wear resistance of mechanisms and machines is being solved on the basis of the use of new composite materials. The most effective method of obtaining composite materials is the use of geological activators, which are introduced into the friction zone of the components of mechanisms and machines through a lubrication system, which allows increasing the micro-moisture of the friction surfaces up to 2,3 times, as well as reducing friction in sliding and rolling bearings. According to the research results, it is found that the use of repair and restoration technologies in friction pairs leads to energy savings of 10–20 %, an increase in wear resistance by 2,5 times, an increase in the resource of lubricants by 2,5–5 times, a significant reduction in vibration noise, as well as an increase in the inter-repair resource by at least 2 times and a reduction in operating costs. However, for the widespread introduction of these technologies, additional studies are needed, which are given in this paper.